Association and outcomes of bacterial infections with acute coronary syndrome; a cross-sectional study from a tertiary care hospital in Pakistan - Sethi, Sher Muhammad; Khanum, Iffat; Javed, Umair; Sabir, Sania (Journal of the Pakistan Medical Association, 2023)
Objective: To identify the association between acute infection and acute coronary syndrome, and to evaluate the outcomes in such cases. Method: The cross-sectional, retrospective, analytical study was conducted at the Aga Khan University Hospital, Karachi, from July to December 2020, and comprised data from January to December 2019 of acute coronary syndrome patients aged >18 years. Data related to demographics, comorbidities, smoking status and history of dyslipidaemia. Binary logistic regression was used to explore the association of infections with acute coronary syndrome. Data was analysed using SPSS 26. Results: Of the 1202 patients with acute coronary syndrome, 189(15.7%) had infection before the coronary event. The mean age of the patients was 68.5±12.4 years, and 97(51.3%) of them were females. Community-acquired pneumonia was found in 105(55.6%) patients, followed by urinary tract infection 64(33.9%) and cellulitis 8(4.2%). For pneumonia, the odds of having non-ST elevated myocardial infarction was 1.1 (95% confidence interval: 0.4-3.0). With urinary tract infections, unstable angina was associated with an odd ratio of 4.2 (95% confidence interval: 1-17.4), and ST elevated myocardial infarction was associated with odd ratio of 3.7 (95% confidence interval: 0.4-31). Conclusion: Bacterial infections were found to be associated with acute coronary syndrome. Bacterial infections with pneumonia and urinary tract infections showed a higher risk of myocardial ischemia. Key Words: Acute coronary syndrome, Bacterial infections, NSTEMI, Pneumonia, STEMI, Urinary tract infections.